The papers of John Hatsell, Clerk of the House of Commons - Hatsell, John 1743-1820 (Cambridge University Press, 2020)
John Hatsell (1733-1820) held the office of Clerk of the House of Commons from 1768 to 1820. In his letters and Memorabilia entries-published here for the first time-Hatsell brought to bear his intimate familiarity with high politics during the reign of George III. Hatsell's expertise in financial policy inspired him to offer counsel to Pitt the Younger during Pitt's first premiership (1783-1801). Hatsell's other correspondents include Henry Addington (speaker 1789-1801 and prime minister 1801-1804), Charles Abbot (speaker 1802-1817), and William Eden (diplomat and President of the Board of Trade in the Ministry of All the Talents, 1806-1807). Hatsell centres his attention on the enduring constitutional significance of the changes he experienced in his public and private life. Hatsell's wry humour is often on display as he reveals the lighter side of social and political life in Great Britain.
Keywords: Hatsell, John -- 1743-1820; Großbritannien -- Parliament -- House of Commons; Geschichte 1761-1820; Schriftgut; Hatsell, John / 1743-1820; Great Britain / Parliament / House of Commons / History / 19th century / Sources; Great Britain / Politics and government / 1789-1820 / Sources; Grande-Bretagne / Sources; Quelle